Relationship between Chronic Energy Deficiency (CED) with Pregnant Women and Abortion - Qurrotul Aini; Mega Silvian Natalia; Tutik Ekasari (Health and Technology Journal (HTechJ), 2023)
The development of health resources in Indonesia today is still marked by the vulnerability to the health status of mothers and children, especially the problem of the still high maternal and infant mortality rates. The causes of maternal death are divided into direct deaths and indirect deaths. One of the causes of maternal death is Chronic Energy Deficiency (CED). The role of nutritional adequacy is very vital, starting from the first trimester of pregnancy to the first thousand days of life. CED in pregnant women can affect the growth process of the fetus and can cause miscarriage. In this study, the researchers aimed to identify a relationship between CED and abortion. This study used a correlation design with a retrospective approach, with a total population of 24 pregnant women with a sample of 24 women who had experienced abortions. The results of the data analysis showed that 66.7% of abortion mothers had CED. the results of the Fisher's Exact Test statistical test obtained a significant degree of the p-value (0.000) < α (0.05) then H1 accepted and H0 rejected, which means that there is a relationship between chronic energy deficiency in pregnant women and the incidence of abortion at the Klenang Kidul Banyuanyar Probolinggo Health Center in 2021-2022. Health workers are expected to carry out prevention efforts by checking the nutritional status of pregnant women regularly and providing knowledge about balanced nutritional needs.